TMCO1-mediated Ca2+ leak underlies osteoblast functions via CaMKII signaling - Jianwei Li (Nature Portfolio, 2019)
TMCO1 is a recently described endoplasmic reticular Ca2+ channel. Here, the authors show it is important for osteoblast function and bone formation in mice, and identify a novel pathway linking local increases in Ca2+ at the ER surface with the posttranslational modification of RUNX2.